Determinants of carbon load in airway macrophages in pregnant women. (15th March 2022) - Miri, Mohammad; Rezaei, Hossein; Momtaz, Seyed Mojtaba; Najafi, Moslem Lari; Adli, Abolfazl; Pajohanfar, Nasim sadat; Abroudi, Mina; Bazghandi, Malihe Sadat; Razavi, Zahra; Alonso, Lucia; Tonne, Cathryn; Basagaña, Xavier; et al.
Abstract: The airway macrophages carbon loading (AMCL) has been suggested to be a biomarker of the long-term exposure to air pollution; however, to date no study has characterized AMCL for the pregnancy period. Therefore, this study aimed to assess the determinants of AMCL during pregnancy in Iran, a middle-income country. This study was based on a sample of 234 pregnant women with term and normal vaginal delivery who were residing in Sabzevar, Iran (2019). We characterized 35 potential determinants of personal exposure to air pollution for each participant, including six personal, nine indoor, and 20 home-outdoor factors. We applied Deletion/Substitution/Addition algorithm to identify the most relevant determinants that could predict AMCL levels. The median (IQR) of AMCL level was 0.12 (0.30) μm 2 with a successful sputum induction in 82.9% (194) of participants. Ambient residential PM2.5 levels were positively associated with higher AMCL levels. On the other hand, increased residential distance to the traffic lights, squares and ring-roads, the duration of opening window per day, and opening window during cooking were inversely associated with AMCL levels. Our findings provide novel insights on the different personal, indoor, and outdoor determinants of personal exposure to air pollution during pregnancy in a middle-income country. Graphical abstract: Image 1 Highlights: Airway macrophage carbon load (AMCL) in 234 pregnant women was assessed. Thirty-five potential determinants of AMCL were investigated. Ambient residential PM2.5 levels was positively associated with higher AMCL levels. Distance to the traffic lights, squares and ring-roads were inversely associated with AMCL levels.